Early Intraorganizational Mobility: Patterns and Influences - Forbes, J. Benjamin (Academy of Management Journal, 1987)
This study examined patterns of early upward mobility for a cohort of 180 employees of an oil company over an 11-year period. The results were not consistent with a strict tournament model of mobility. Later positions were more predictive of career attainment than were early promotions. In addition, initial functional area and the number of different jobs held were related to career attainment. The data supported signaling theory as an explanation of the effects of historical data on decisions about promotions.